Міста Жидачівського повіту XIV–XVI ст. - Капраль, М. (Історико-географічні дослідження в Україні, 2019)
У статті розглядається міська мережа Жидачівського повіту Львівської
землі у Руськомі воєводстві в пізньому середньовіччі та початку ранньомодерного часу. Автор встановив кількість населених пунктів, що одержали міське
маґдебурзьке право. Два найбільші центри – Жидачів та Долина – отримали надання як королівські міста, а шість інших (Стрілища, Ходорів, Журів, Соколів, Монастирець, Журавно, Розділ) були засновані як приватні шляхетські міста.
Загалом Жидачівський повіт залишався одним з найменш урбанізованих регіонів західноукраїнських земель у досліджуваний період. The article deals with urban net of the Zhydachiv district of the Lviv land from the
Ruthenian voievoship in the late middle ages and early modern period. Two main towns
Zhydachiv and Dolyna were investments of royal power, and six others (Strilyshcha,
Khodoriv, Dzhuriv, Sokoliv, Monastyrets, Zhuravno, Rozdil) functioned as private cities.
The towns of the district, located in the Precarpathian region, situated not on the intensive
trade routes of the Ruthenian Palatinate (Ruske voievodstvo) in the direction to Moldavian
Principality and the Ottoman Porte, which led somewhat eastward. Their functions were
limited, for the most part, to servicing the local market and defense against attacks from
the south, first of all, Tatars and less Moldavian troops. An important restriction to the
development of the city network was the lack of powerful magnate families who could
invest in the development of the region. Having these circumstances, the Zhydachiv
district remained one of the most weak in the urban development of the all districts in
the Ruthenian voievoship during the 14–16th centuries.